A CIRCULATION-FIRST APPROACH FOR RESUSCITATION OF TRAUMA PATIENTS WITH HEMORRHAGIC SHOCK. Issue 1 (28th January 2023) - Chio, Jonathon Chon Teng; Piehl, Mark; De Maio, Valerie J.; Simpson, John T.; Matzko, Chelsea; Belding, Cameron; Broome, Jacob M.; Duchesne, Juan
ABSTRACT: The original guidelines of cardiopulmonary resuscitation focused on the establishment of an airway and rescue breathing before restoration of circulation through cardiopulmonary resuscitation. As a result, the airway-breathing-circulation approach became the central guiding principle of resuscitation. Despite new guidelines by the American Heart Association for a circulation-first approach, Advanced Trauma Life Support guidelines continue to advocate for the airway-breathing-circulation sequence. Although definitive airway management is often necessary for severely injured patients, endotracheal intubation (ETI) before resuscitation in patients with hemorrhagic shock may worsen hypotension and precipitate cardiac arrest. In severely injured patients, a paradigm shift should be considered, which prioritizes restoration of circulation before ETI and positive pressure ventilation while maintaining a focus on basic airway assessment and noninvasive airway interventions. For this patient population, the most reasonable current strategy may be to target a simultaneous resuscitation approach, with immediate efforts to control hemorrhage and provide basic airway interventions while prioritizing volume resuscitation with blood products and deferring ETI until adequate systemic perfusion has been attained. We believe that a circulation-first sequence will improve both survival and neurologic outcomes for a traumatically injured patient and will continue to advocate this approach, as additional clinical evidence is generated to inform how to best tailor circulation-first resuscitation for varied injury patterns and patient populations.